A theoretical growth model for Ireland - Barry, Frank; Devereux, Michael B. (Economic & Social Studies, 2006)
Ireland is distinguished by the high degree of openness of its labour market and the importance of foreign direct investment (FDI) in the economy. We develop a neo-classical growth model to explore the consequence of these characteristics for the response of an economy to the kinds of shocks that are widely recognised to have been of importance in driving the Irish boom.
An earlier version was presented at the Conference on Macroeconomic Perspectives in Honour of Brendan M. Walsh, held at University College Dublin on 7 October, 2005
Keywords: Growth model; Macroeconomic policy; Ireland; Exogenous growth